Severe Acute Respiratory Syndrome Coronavirus 2 RNA in Plasma Is Associated With Intensive Care Unit Admission and Mortality in Patients Hospitalized With Coronavirus Disease 2019. (5th September 2020) - Prebensen, Christian; Myhre, Peder L; Jonassen, Christine; Rangberg, Anbjørg; Blomfeldt, Anita; Svensson, My; Omland, Torbjørn; Berdal, Jan-Erik
Abstract: The clinical significance of severe acute respiratory syndrome coronavirus 2 RNA in the circulation is unknown. In this prospective cohort study, we detected viral RNA in the plasma of 58 of 123 (47%) patients hospitalized with coronavirus disease 2019. RNA was detected more frequently, and levels were higher, in patients who were admitted to the intensive care unit and/or died.